(untitled) (Medical Forum Monthly, 2024)
Objective: To study the Role of Paravertebral Blocks after Unilateral Modified Radical Mastectomy for Breast Cancer. Study Design: Descriptive case series Place and Duration of Study: This study was conducted at the Department of Surgical Unit 2, Jinnah hospital Lahore from 1st February 2017 to 31th January 2018. Materials and Methods: The study was conducted among 100 female breast cancer patients undergoing unilateral modified radical mastectomy. Paravertebral blocks were given by 0.5% bupivacaine from 2nd to 7th paravertebral spaces. Patients were observed for Pain scorein first 24hour periodby Visual Analogue Scale(VAS). The VAS scoring at first rescue analgesic, duration of post-operative analgesia, frequency of analgesia administration and mean consumption of analgesia in first 24 hours period were calculated. Results: Out of 100 patients, 65% of the patients belong to age group 35-50 years and only 35% of the patients belong to age group 51-65 years age group. The mean of the VAS scoring at first rescue analgesic was 5.58 ±0.781.The duration of post-operative analgesia was 5.15±1.104 hours (309±66.42 min). The frequency of analgesic administration was 3.53± 1.104. The mean consumption of analgesic given to all patients was 88.22 ±22.32. Conclusion: The study has demonstrated that the paravertebral blocks lead to prolonged post op analgesia with marked reduction in post op analgesic requirement. Key words: Para vertebral Blocks, Modified Radical Mastectomy, Breast Cancer. Visual Analogue Score.